Eclipse of comunity : an interpretation of American studies - Stein, Maurice R. (New Jersey, 1960)
This book interprets the problems and prospects of Ameri can community life, using field studies conducted by sociolo gists during the past half century. Shapes and forces of change are explored as they fashion the destinies of persons living in settings ranging from small towns to great cities and from impoverished urban slums to prosperous suburbs. Anthropo logical and psychoanalytic perspectives are used to illuminate deeper meanings of recent trends. The analysis proceeds by comparing the dominant myths in each community with rele vant social realities. Familiarizing ourselves with many such patterns helps to nourish the kind of sociological imagination needed for examining the contrasts between myths and reali ties in our own communities. We should not let the fact that we cannot predict the exact outcome of the present eclipse dissuade us from trying to see as far ahead as we possibly can.
Keywords: Community development